Hollow Plasmonic U‐Cavities with High‐Aspect‐Ratio Nanofins Sustaining Strong Optical Vortices for Light Trapping and Sensing. Issue 6 (19th April 2014) - Ho, Ya‐Lun; Portela, Alejandro; Lee, Yaerim; Maeda, Etsuo; Tabata, Hitoshi; Delaunay, Jean‐Jacques
<x xml:space="preserve">Abstract</x> Coupling of ridge hot spots with a scalable resonant U‐cavity fully traps light in intense optical vortices, generating strong and sharp resonances with widths as small as 14 nm. Tunable resonance wavelengths from visible to near‐infrared are achieved by controlling the cavity dimensions. Sensing performance with a figure of merit of 136 is attained and biosensing in a protein‐ligand scheme is demonstrated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>